Plans for the Riverside of Lisbon. Ancient Quays at Terreiro do Paço and Belém - Antunes, Alexandra de Carvalho (2017)
This book presents the plans for the riverside of Lisbon and also for the River Tagus quays prior to the 1755 earthquake. Various stone quays at Terreiro do Paço are referred to and, examined for the first time, the imposing, previously unknown, and now lost Royal Quay at Belém, which had been located in front of the present Presidential Palace. The unpublished documents and illustrations used in this research are introduced herein.